Frequency of the Congenital Transmission of Trypanosoma cruzi: A Systematic Review and Meta-Analysis - Howard, Elizabeth J. (2013)
BACKGROUND: Chagas disease is caused by the parasite Trypanosoma cruzi and endemic in much of Latin America. With increased globalization and immigration, it is a risk in any country due in part to congenital transmission. The frequency of congenital transmission is unclear. OBJECTIVE: To assess the frequency of congenital transmission of T. cruzi. SEARCH STRATEGY: PubMed, Journals@Ovid Full Text, EMBASE, CINAHL, Fuente Academica and BIREME databases were searched using seven search terms related to Chagas disease or Trypanosoma cruzi and congenital transmission. SELECTION CRITERIA: The inclusion criteria were the following: Dutch, English, French, Portuguese or Spanish language; case report, case series or observational study; original data on congenital T. cruzi infection in humans; congenital infection rate reported or it could be derived. This systematic review included 13 case reports/series and 51 observational studies. DATA COLLECTION AND ANALYSIS: Two investigators independently collected data on study characteristics, diagnosis and congenital infection rate. The principal summary measure – the congenital transmission rate – is defined as the number of congenitally infected infants divided by the number of infants born to infected mothers. A random effects model was utilized. MAIN RESULTS: The pooled congenital transmission rate was 4.7% (95% confidence interval: 3.9–5.6%). Endemic countries had a higher rate of congenital transmission compared to non-endemic (5.0% vs. 2.7%). CONCLUSIONS: Congenital transmission of Chagas disease is a global problem. Overall risk of congenital infection in infants born to infected mothers is about 5%. The congenital mode of transmission requires targeted screening to prevent future cases of Chagas disease.